Eurasian mid-latitude jet stream bridges an Atlantic to Asia summer teleconnection in heat extremes - Yu Nie; Hong-Li Ren; Jinqing Zuo; Jie Wu; Adam A Scaife; Nick J Dunstone; Steven C Hardiman (Environmental Research Letters, 2024)
Northern Europe and Northeast Asia, which are climatologically mild and temperate in early summer, both witnessed record-breaking heat extremes in June 2023. With a focus on the subseasonal time scale, this study highlights a teleconnected relationship in historical early-summer heat extremes between Northern Europe and Northeast Asia. By diagnosing the thermal budget and wave activity flux, we show that over one third of historical Northeast Asian heat extremes are initialized by Eurasian mid-latitude Rossby wave packets. The wave packets manifest as strong anticyclonic anomalies over subpolar North Atlantic, cyclonic anomalies over Ural region and anticyclonic anomalies over Northeast Asia, which directly cause coexisting heat extremes in Northern Europe and Northeast Asia. Such wave packets are strongly modulated by the Eurasian jet stream. By carrying out numerical experiments, we further explain why the wave packet is significant in early summer. We find that the quasi-stationary response of the Eurasian midlatitude Rossby wave packets to a specified heating in subpolar North Atlantic is dependent on the background jet structure. In early summer, the double-jet state over Eurasia favors Rossby wave propagation. This is of great practical importance for accurate prediction of Northeast Asian heat extreme amplitude and location.